Randomised, double-blind, phase III study comparing the infliximab biosimilar, PF-06438179/GP1111, with reference infliximab: efficacy, safety and immunogenicity from week 30 to week 54 - Goran Babic; Hideto Kameda; Rieke Alten; Bogdan Batko; Tomas Hala; Sebastiao C Radominski; Vira Tseluyko; Carol Cronenberger; Sarah Hackley; Muhammad Rehman; Oliver von Richter; Min Zhang; et al. (RMD Open, 2019)
Objective To investigate the efficacy, safety and immunogenicity of PF-06438179/GP1111 (PF-SZ-IFX) compared with European reference infliximab (Remicade®; ref-IFX) in patients with moderate-to-severe, active rheumatoid arthritis after continued long-term use of PF-SZ-IFX, and in patients who were switched from ref-IFX to PF-SZ-IFX.Methods REFLECTIONS B537-02 was a double-blind, active-controlled, multinational study in which patients (N=650) were initially randomised to PF-SZ-IFX or ref-IFX for 30 weeks (treatment period [TP] 1). During weeks 30–54 (TP2), the PF-SZ-IFX group (n=280) continued treatment with PF-SZ-IFX (PF-SZ-IFX/PF-SZ-IFX) and patients in the ref-IFX group (n=286) were rerandomised (1:1) to continue ref-IFX (ref-IFX/ref-IFX) (n=143) or switch to PF-SZ-IFX (ref-IFX/PF-SZ-IFX) (n=143) for a further 24 weeks. Efficacy, safety, immunogenicity and pharmacokinetics were evaluated.Results During TP2, patients in all three treatment groups continued to maintain comparable treatment response. At week 54, the American College of Rheumatology (ACR20) response rates were 71.1% (PF-SZ-IFX/PF-SZ-IFX), 64.3% (ref-IFX/ref-IFX) and 70.6% (ref-IFX/PF-SZ-IFX). Observations for other endpoints, including ACR50/70, Disease Activity Score in 28 Joints Based on High-Sensitivity C Reactive Protein(DAS28-CRP) remission, and mean change in DAS28-CRP and Health Assessment Questionnaire-Disability Index, were also comparable. Treatment-emergent adverse events were reported in 36.8% (PF-SZ-IFX/PF-SZ-IFX), 33.6% (ref-IFX/ref-IFX) and 37.8% (ref-IFX/PF-SZ-IFX) of patients; there were no clinically meaningful differences in the safety profiles between groups. The percentage of patients who were antidrug antibody-positive was generally stable through the treatment period and comparable overall between the PF-SZ-IFX/PF-SZ-IFX (52.1%; neutralising: 80.8%), ref-IFX/ref-IFX (60.1%; neutralising: 84.9%) and ref-IFX/PF-SZ-IFX (58.0%; neutralising 78.3%) groups.Conclusions The similar efficacy, safety and immunogenicity of PF-SZ-IFX compared with ref-IFX were maintained for up to 54 weeks and were not affected by blinded treatment switch from ref-IFX to PF-SZ-IFX at week 30.Trial registration number NCT02222493.